Association of Neutrophil Lymphocyte Ratio (NLR) with Global Registry of Acute Coronary Events (GRACE) Scores in Acute Coronary Syndrome - Baginda Yusuf Siregar; Refli Hasan; Rahmad Isnanta (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Background. Inflammation plays an important role in the initiation of atherosclerosis from the beginning of plaque to rupture cause Acute Coronary Syndrome (ACS). Neutrophil Lymphocyte Ratio (NLR) indicator of systemic inflammation in ACS. Risk stratification was needed for assessment and selection of initial invasive strategies and find the best strategy in ACS. The Global Registry of Acute Coronary Events (GRACE) scores recommended risk stratification of ACS. Aims of the study to determine the association and cut-off value NLR with risk stratification GRACE score. Method. This study is analytical with a cross-sectional retrospective design. Data were analyzed after distribution test, then mean difference and correlation test was using the SPPS program where p <0.05 was considered statistically significant. Results. This study showed significantly higher NLR value in the high risk stratification and intermediate-risk compared to low risk stratification (7.9 ± 2.7 vs 3.6 ± 1.7; p=0.001) (5.2 ± 2.3 vs 3.6 ± 1.7; p=0.018). Significant correlation between NLR ​​with GRACE scores (r=0.570; p<0.001). Significant AUC values ​​were obtained (0.782, p <0.001, IK95% 0.674-0.89), and cut-off values NLR 4 ​​with sensitivity (78.8%) and specificity (70.3%) on the GRACE score. Conclusion. The significant association between NLR ​​with GRACE risk score in ACS.